Keniscayaan Metode Komprehensif dalam Studi Islam: Telaah Pemikiran Ali Syariati - Zulkifli Abdurrahman Usman (Program studi Keagamaan Islam, 2022)
This article reveals Ali Shariati's thoughts on methodological issues in studying Islam. The data used are the works of Ali Shariati and relevant literature obtained from library sources and analyzed by qualitative descriptive methods and philosophical approaches. This article finds that Ali Shariati views it as important and necessary to understand Islam in various ways. According to him, the method of understanding Islam is fundamental for socio-political change and the progress of civilization. However, Ali Shariati only offers two approaches to understanding Islam, namely historical and sociological approaches. Based on these findings, this article recommends and supports the claims of urgency and necessity of comprehensive methods in Islamic studies